1990
DOI: 10.3109/00498259009046892
|View full text |Cite
|
Sign up to set email alerts
|

In vitrometabolism of the antianxiety drug buspirone as a predictor of its metabolismin vivo

Abstract: 1. Metabolism of the antianxiety drug buspirone was studied by in vitro incubations with rat liver microsomes and hepatocytes. Metabolites were isolated and purified by h.p.l.c. The purified metabolites were identified by co-elution on h.p.l.c. with authentic standards and by g.l.c.-electron impact mass spectrometry of their trimethylsilyl (TMS) derivatives. 2. Five metabolites of buspirone were identified in the microsomal incubates and seven in the hepatocyte incubates. The major metabolites arose from aroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…These data suggest that N-dealkylation to form 1-PP and hydroxylation to form multiple monohydroxylated metabolites are the primary metabolic pathways responsible for buspirone clearance in humans and rats. In vitro metabolism of buspirone in rats has been investigated in several systems prepared from liver tissues, including S-9 preparation (Kerns et al, 1997), liver slices (Goldthwaite et al, 1996), microsomal preparation, and hepatocytes (Jajoo et at., 1990). Major in vitro metabolic reactions in rats are the formation of 1-PP, 3Ј-OH-Bu, 5-OH-Bu, and 6Ј-OH-Bu, consistent with the in vivo metabolism pathways in rats (Jajoo et al, 1989a).…”
mentioning
confidence: 99%
“…These data suggest that N-dealkylation to form 1-PP and hydroxylation to form multiple monohydroxylated metabolites are the primary metabolic pathways responsible for buspirone clearance in humans and rats. In vitro metabolism of buspirone in rats has been investigated in several systems prepared from liver tissues, including S-9 preparation (Kerns et al, 1997), liver slices (Goldthwaite et al, 1996), microsomal preparation, and hepatocytes (Jajoo et at., 1990). Major in vitro metabolic reactions in rats are the formation of 1-PP, 3Ј-OH-Bu, 5-OH-Bu, and 6Ј-OH-Bu, consistent with the in vivo metabolism pathways in rats (Jajoo et al, 1989a).…”
mentioning
confidence: 99%
“…Nefazodone bioactivation by CYP3A4 is also accompanied by mechanism-based inactivation of the isozyme, which is consistent with DDIs between nefazodone and CYP3A4 substrates [67] [68]. As in the case of nefazodone, para-hydroxybuspirone also represents a major circulating metabolite of the anxiolytic agent buspirone (Scheme 7) [69]. However, the failure to detect GSH conjugates in microsomal incubations of buspirone suggests that the drug is not prone to bioactivation [65].…”
Section: Bioactivation Of the Calcium-channel Opener Maxipost In Rat mentioning
confidence: 80%
“…Buspirone is extensively metabolized when orally dosed to rats. [24] In addition to the major metabolites included in this study, there are many other oxidative metabolites found in vitro and in vivo. In order to use UV peak area to correct for the mass spectrometry response of one metabolite, it is very important to ensure Table 1) and (B) mass accuracy of internal standard buspirone-D 8 in one analytical run consisting of 99 samples.…”
Section: Quantitative Estimation Of Metabolite Exposure Using Uv Corrmentioning
confidence: 99%